Kelangsungan bahasa Melayu dalam sistem pendidikan Malaysia - Alis Puteh, 1959 (Kuala Lumpur :: Dewan Bahasa dan Pustaka, 2015)
On Malay language in education in Malaysia.
Includes bibliographical references (pages 307-342) and index.
In Malay.
Keywords: Malay language -- Study and teaching